2009
DOI: 10.1111/j.1471-4159.2009.05843.x
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminases and neurodegeneration

Abstract: Eight active transglutaminases (TGs) (TGs 1-7 and factor XIIIa) are expressed in mammals, of which TGs 1-3 (Kim et al. 1999) 1 and 6 (Hadjivassilou et al. 2008) are present in human brain. The major reaction thus far attributed to the cerebral TGs is transamidation. In this reaction the carboxamide moiety of a Q residue [-C(O)NH 2 ] is converted to a substituted carboxamide [-C(O)NHR] by nucleophilic attack of an amine [RNH 2 ] such as various mono-, di-, and polyamines or the e amino group of a K residue (Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 93 publications
(181 reference statements)
1
70
0
Order By: Relevance
“…It has been reported that TG activity is significantly elevated in the affected cerebral regions in Alzheimer disease, Huntington disease and supranuclear palsy (Jeitner et al, 2009). In addition, increased TG2 protein is observed in the cerebrospinal fluid of Alzheimer disease (Bonelli et al, 2002) and Parkinson disease subjects (Vermes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TG activity is significantly elevated in the affected cerebral regions in Alzheimer disease, Huntington disease and supranuclear palsy (Jeitner et al, 2009). In addition, increased TG2 protein is observed in the cerebrospinal fluid of Alzheimer disease (Bonelli et al, 2002) and Parkinson disease subjects (Vermes et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, TG 1-3 and 6 were discovered in human brain (Hadjivassiliou et al, 2008). In addition to SCA, TGs are also hypothesized to be involved in the pathogenesis of several other neurodegenerative diseases, including polyglutamine expansion diseases, Alzheimer's, Parkinson's and supranuclear palsy (Jeitner et al, 2009). However, despite extensive investigation over the last two decades, the physiologic or pathologic roles of TGs in the brain remain unclear.…”
mentioning
confidence: 99%
“…7 TG2 overactivity has been associated with inflammatory disease processes such as celiac disease, infectious diseases, cancer, and neurodegenerative diseases such as Huntington's disease (HD). [8][9][10][11] HD is an autosomal dominant, progressive neurodegenerative disease that is characterized clinically by motor, cognitive, and behavioral deficits. Specifically, TG2 expression and transglutaminase activity have been shown to be increased in the brains of HD patients and in HD mouse models.…”
mentioning
confidence: 99%
“…Our data indicated that the modification by TG2 impaired IP 3 R1-mediated cellular processes; therefore, we hypothesized that this regulation might lead to cellular dysregulation under pathological conditions. TG2 is up-regulated in the brain in HD model mice, including R6/2 and YAC128 mice (54)(55)(56)(57), and HD patients (49,(58)(59)(60)(61). Therefore, we tested whether IP 3 R was modified by TG2 in these HD models.…”
Section: Resultsmentioning
confidence: 99%
“…S1 A-C). The Ca 2+ dependence, elution profile of the activity, and inhibition with cystamine led us to postulate that the crosslinking might be catalyzed by a TG, most likely TG2 (34,49).…”
Section: Resultsmentioning
confidence: 99%